Flexible transparent displays based on core/shell upconversion nanophosphor-incorporated polymer waveguides - Park, Bong Je; Hong, A-Ra; Park, Suntak; Kyung, Ki-Uk; Lee, Kwangyeol; Jang, Ho Seong (NATURE PUBLISHING GROUP, 2017)
Core/shell (C/S)-structured upconversion nanophosphor (UCNP)-incorporated polymer waveguidebased flexible transparent displays are demonstrated. Bright green-and blue-emitting Li(Gd, Y) F-4: Yb, Er and Li(Gd, Y) F-4: Yb, Tm UCNPs are synthesized via solution chemical route. Their upconversion luminescence (UCL) intensities are enhanced by the formation of C/S structure with LiYF4 shell. The Li(Gd, Y) F-4: Yb,Er/LiYF4 and Li(Gd, Y) F-4: Yb, Tm/LiYF4 C/S UCNPs exhibit 3.3 and 2.0 times higher UCL intensities than core counterparts, respectively. In addition, NaGdF4: Yb, Tm/NaGdF4: Eu C/S UCNPs are synthesized and they show red emission via energy transfer and migration of Yb3+-> Tm3+-> Gd3+-> Eu3+. The C/S UCNPs are incorporated into bisphenol A ethoxylate diacrylate which is used as a core material of polymer waveguides. The fabricated stripe-type polymer waveguides are highly flexible and transparent (transmittance > 90% in spectral range of 443-900 nm). The polymer waveguides exhibit bright blue, green, and red luminescence, depending on the incorporated UCNPs into the polymer core, under coupling with a near infrared (NIR) laser. Moreover, patterned polymer waveguide-based display devices are fabricated by reactive ion etching process and they realize bright blue-, green-, and red-colored characters under coupling with an NIR laser.
Keywords: LANTHANIDE-DOPED NANOCRYSTALS; CORE-SHELL NANOPARTICLES; IN-VIVO; OPTICAL-PROPERTIES; ENERGY MIGRATION; SOLID-STATE; LIGHT; LUMINESCENCE; COMPOSITES; NANOPROBES